PROFESSIONAL SOCIALIZATION AS A CONDITION OF FORMATION GRADUATES’ COMPETITIVENESS - I. Yu. Stepanova; V. A. Adolf (Высшее образование в России)
The quality of graduates’ training is often criticized by employers. A graduate of higher education system has a choice of the further professional trajectory but does not understand how to use it when he enters the labor market. We believe that the reason for that is the lack of attention to the problems of professional socialization during the education period. In this context, there is a need to create conditions for implementation by students of dialectic synthesis of socialization and individualization in relation to solving the problems of constructing a career path. The article proposes to connect the solution of the indicated problems with the passing by students the procedures of self-determination regarding the types of the mastered activities according to the requirements of educational programs. The article reveals the complexity of the implementation of the proposed process and explains the need for its implementation to achieve graduates’ competitiveness as the predicted educational result.